Theatres of opposition empire, revolution, and Richard Brinsley Sheridan - Taylor, David Francis (Oxford : Oxford University Press, 2012)
This study considers Richard Brinsley Sheridan's theatrical and political commitments side by side. It offers a challenging new take on a misunderstood writer and presents important new insights into the relationship between theatre and parliament in the 18th century.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Sheridan, Richard Brinsley, -- 1751-1816 -- POlitical activity; Sheridan, Richard Brinsley, -- 1751-1816 -- Political and social views; Politics and literature -- Great Britain -- History -- 18th century